Surface-enhanced Raman and DFT study on zidovudine. Issue 4 (2011) - Mircescu, Nicoleta Elena; Varvescu, Andrada; Herman, Krisztian; Chiş, Vasile; Leopold, Nicolae
Abstract : This work presents a surface-enhanced Raman scattering (SERS) and density functional theory (DFT) study on neutral and deprotonated molecular forms of zidovudine. A p K a value of 9.55 was found for this compound, the deprotonation occurring at the imide nitrogen of the pyrimidine ring. The characteristic bands of the SERS spectra were assigned considering both, the calculated vibrational wavenumbers and Raman intensity pattern. The adsorption geometry on the silver surface of zidovudine was derived based on the molecular electrostatic potential (MEP) and the selective Raman bands enhancement.